PENGGUNAAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BILANGAN BULAT DI KELAS IV SD NEGERI 2 MERGOSONO - Putri, Tyas Anggoro (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The use of Realistic Mathematics Education Approach with Concrete Media in Improvement Mathematics Learning About Integers of fourth Grade SD Negeri 2 Mergosono. This study aims: (1) to describe the process of learning, (2) improving the learning of mathematics, and (3) the constraints and solutions. This research was conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. Subjects were students in the fourth grade elementary school with 29 students. Source of data derived from the document, students, and colleagues. The data collection technique is to test, observation, interviews, and documentation. Analysis of the data used by the qualitative and quantitative analysis. The percentage of student mastery before action was 24.14%, after the implemented action first cycle increased to 65.52%, the second cycle increased to 82.76% and the third cycle increased to 93,10%. The results show that: realistic mathematics education that approach with concrete media can improve math learning about integers in fourth grade primary schools students. Keywords: mathematical approach realistic, Concrete Media, Integers Abstrak: Penggunaan Pendekatan Pendidikan Matematika Realistik (PMR) dengan Media Konkret dalam Peningkatan Pembelajaran Matematika Tentang Bilangan Bulat Di Kelas IV SD Negeri 2 Mergosono. Penelitian ini bertujuan : (1) mendeskripsikan proses pembelajaran, (2) peningkatan pembelajaran matematika, dan (3) kendala dan solusinya. Penelitian ini dilaksanakan dalam tiga siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah siswa kelas IV SD Negeri 2 Mergosono dengan 29 siswa. Sumber data berasal dari dokumen dan siswa. Teknik pengumpulan data adalah dengan tes, observasi, wawancara, dan dokumentasi. Analisis data yang digunakan dengan analisis kualitatif dan kuantitatif. Persentase ketuntasan siswa sebelum tindakan adalah 24,14%, setelah dilaksanakan tindakan siklus I meningkat menjadi 65,52%, siklus II meningkat menjadi 82,76% dan siklus III meningkat kembali menjadi 93,10%. Hasilnya menunjukkan bahwa Pendekatan pendidikan matematika realistik dengan media konkret dapat meningkatkan pembelajaran matematika tentang bilangan bulat pada siswa kelas IV sekolah dasar. Kata Kunci: Pendekatan Matematika Realistik, Media Konkret, Bilangan Bulat.